2012
DOI: 10.2139/ssrn.2054436
|View full text |Cite
|
Sign up to set email alerts
|

Stock Return Comovement and Systemic Risk in the Turkish Banking System

Abstract: This paper investigates the evolution of systemic risk in the Turkish banking sector over the past two decades using comovement of banks' stock returns as a systemic risk indicator. In addition, we explore possible determinants of systemic risk, the knowledge of which can be a useful input into effective macroprudential policymaking. Results show that the correlations between bank stock returns almost doubled in 2000s in comparison to 1990s. The correlations decreased somewhat after 2002 and increased again as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The results concluded that SES is a powerful systemic risk alternative approach. Binici et al. (2013) survey the development of systemic risk in the Turkish banking sector using co-movement of the stock returns of banks and search the possible determinants of systemic risk.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results concluded that SES is a powerful systemic risk alternative approach. Binici et al. (2013) survey the development of systemic risk in the Turkish banking sector using co-movement of the stock returns of banks and search the possible determinants of systemic risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results concluded that SES is a powerful systemic risk alternative approach. Binici et al (2013) survey the development of systemic risk in the Turkish banking sector using co-movement of the stock returns of banks and search the possible determinants of systemic risk. As a result, they find the main determinants of systemic risk: the market share of bank pairs, the amount of non-performing loans, heard of behavior of banks, and the volatilities of macrovariables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the developing countries, industry structure is pretty simple and is inevitably to be affected by the system risks like the financial crisis (Mahir Binici, Bülent Köksal and Cüneyt Orman, 2012) [11]. For example, recently in China, the percentage of import oil to the total number of oil is about 60 % (the National Bureau of Statistics of China), which means China pretty rely on oil import.…”
Section: The System Risksmentioning
confidence: 99%
“…The results show non-negligible cross-asset market relations during distress times. Binici et al (2013) examine the systemic risk status of the Turkish banking sector during the last two decades running a new systemic risk indicator which is defined as co-movement of banks' stock returns. In the study, the daily share prices of the seventeen banks quoted on the Turkish stock market are used between 1990 and 2011.…”
Section: Introductionmentioning
confidence: 99%